Correlation between Serum hs-CRP and Magnesium Ion with Osteocalcin in Acute Leukemia Patients - Nuniek Luthy Naftali; MI. Diah Pramudianti; Yuwono Hadisuparto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Acute leukemia is a proliferation of immature cells in the bone marrow that affects peripheral blood or other organs. Inflammation has a vital role in cancer pathophysiology. Inflammation in leukemia occurs through two mechanisms: intrinsic and extrinsic. Magnesium deficiency leads to inflammation in acute leukemia patients. Manifestation of inflammation in acute leukemia are abnormalities in musculoskeletal systems such as osteopenia, osteoporosis, osteonecrosis, and pathological fractures. Increased inflammation in the bone remodeling process increases osteoclast (OC) regulation and decreases osteoblast (OB) activity resulting in reduced osteocalcin (OCN) production. Osteocalcin, also known as gamma-carboxy glutamic acid-containing protein or bone Gla-protein, is a small, non-collagen protein associated with the bone matrix. Osteocalcin is known as bone formation. This study aimed to analyze the correlation between hs-CRP, ion Mg and serum OCN levels in acute leukemia. A cross-sectional observational analytic study in acute leukemia subjects was conducted at Clinical Pathology Installation of Dr. Moewardi Hospital. Surakarta from August to September 2020. Normality test of Shapiro-Wilk was used to determine data distribution, Pearson correlation test was used to analyze the correlation strength between variables. From a total of 35 subjects, there was a significant negative correlation between hs-CRP and serum OCN in acute leukemia (r= -0.46; p=0.06), but no correlation was found between Mg ion and serum OCN in acute leukemia patients (r=0.09; p=0.957). The mean of hs-CRP, Mg ion, and OCN was 2.95±4.95 mg/dL, 0.49±0.05 mmol/L, and 16.32±19.46 ng/mL, respectively. Advanced research with chronic leukemia population and other variants as needed.